Preparation and investigation of photoelectrochemical behaviour of Ce and W co-doped TiO2 composite film - Hasan, M.R. (Maney Publishing, 2014)
Cerium and tungsten co-doped TiO2 photocatalyst composite material has been fabricated by using a facile sol-gel method. The composite was coated on ITO film via electrophoretic deposition method. In order to understand the morphology, structure and optical properties, the composite material was characterized with X-ray diffraction, scanning electron microscope, UV-vis and Fourier transform infrared spectroscopy. The results showed a uniformly distributed porous composite film on ITO substrate. Cerium and tungsten as oxides are dispersed on the substrate. A significant photocurrent was developed under solar simulator irradiation and the value was observed higher as compared with pure TiO2 film electrodes.